One for all or all for one? An integrative review of research on frequent callers - S. Skogevall; E. Kaminsky; J. Håkansson; I.K. Holmström (Elsevier, 2022)
Objective: Telephone health services is an increasing and integral part of health care in several countries. Callers who call repeatedly, in the current study "frequent callers" are present in all kinds of healthcare services, often constitute a considerable proportion of the total amount of calls and are complicated to help. The aim was to provide a comprehensive overview of research on frequent callers at a variety of telephone health services. Methods: An integrative literature review. Literature was searched for the period 2011-2020 in CINAHL Plus, MEDLINE, APA PsycArticles, APA PsycInfo, and PubMed, and resulted in the inclusion of 20 articles. Results: Studies on frequent callers (FCs) were found in the context of emergency medical services, telephone helplines, primary healthcare, and specialist medicine clinics. Frequent calling was associated with psychiatric comorbidity, and the reasons for calling were often multifaceted. Conclusion: The strategies suggested for handling calls involved an individual approach, which could be enabled through multidisciplinary work. Innovation: The main findings indicate a need for a systematic approach and guidelines to enable optimal help for FCs. Cooperation among healthcare instances seems to contribute to a more individual care for FCs.